Antimicrobial Stewardship in Acute Care Centres: A Survey of 68 Hospitals in Quebec - Vincent Nault; Mathieu Beaudoin; Daniel JG Thirion; Michel Gosselin; Benoit Cossette; Louis Valiquette (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Antimicrobial stewardship programs (ASPs) and quantitative monitoring of antimicrobial use are required to ensure that antimicrobials are used appropriately in the acute care setting, and have the potential to reduce costs and limit the spread of antimicrobial-resistant organisms and Clostridium difficile. Currently, it is not known what proportion of Quebec hospitals have an ASP and/or monitor antimicrobial use.